Jurulatih senaman maya berasaskan teknologi sensor dan aplikasi pintar interaktif (Virtual exercise trainer using sensor-based and interactive smartphone application technology) / Adam Linoby …[et al.] - Linoby, Adam; Kusrin, Jamiaton; Asraff, Muhammad Iskandar; Rodzi, Muhammad Azamuddin; Zaki, Sufyan; Hasan, Hosni (Universiti Teknologi MARA, 2020)
The use of electronic monitoring instruments in conventional exercise training equipments has had a positive influence on user interest level, subsequently increasing the overall exercise experience and performance. Accordingly, the most beneficial results of any exercise are obtained when an individual is given a specific, easily understandable performance target, is informed of the exercise progress, and is given verbal motivation, coaching, encouragement, and instruction. However, conventional electronic monitoring instruments do not serve to directly motivate or coach the individual to complete an exercise program. Moreover, such a device is of limited use in non-cardiovascular, strength training exercise equipment (e.g free weights and isometric exercises). The present invention responds to this problem by providing a smart motion sensor magnetically retrofittable into exercise apparatus such as a dumbbell, or as part of a piece of exercise equipment, such as a metal handle of exercise equipment that undergoes reciprocal movement. This sensor will continuously transmit a signal to an application in user’s smart device, which then correspondingly generated guided instructional, interactive feedback as well as motivational visual and audio output with respect to various physical exercise a user might undertake. The development of such a practical 2 exercise system would certainly help the active individual, clinical population, athletes, aging and sedentary population to implement a more effective, interactive and safer exercise training regime.